Continuous Production of Long-Side-Chain Poly-β-Hydroxyalkanoates by Pseudomonas oleovorans - Ramsay, Bruce A. (1991)
Shake flask experiments showed that Pseudomonas oleovorans began to be growth inhibited at 4.65 g of sodium octanoate liter(-1), with total inhibition at 6 g liter(-1). In chemostat studies with 2 g of ammonium sulfate and 8 g of octanoate liter(-1) in the feed, the maximum specific growth rate was 0.51 h(-1), and the maximum specific rate of poly-β-hydroxyalkanoate (PHA) production was 0.074 g of PHA g of cellular protein(-1) h(-1) at a dilution rate (D) of 0.25 h(-1). When the specific growth rate (μ) was <0.3 h(-1), the PHA composition was relatively constant with a C(4)/C(6)/C(8)/C(10) ratio of 0.1:1.7:20.7:1.0. At μ > 0.3 h(-1), a decrease in the percentage of C(8) with a concomitant increase in C(10) monomers as μ increased was probably due to the effects of higher concentrations of unmetabolized octanoate in the fermentor. At D = 0.24 h(-1) and an increasing carbon/nitrogen ratio, the percentage of PHA in the biomass was constant at 13% (wt/wt), indicating that nitrogen limitation did not affect PHA accumulation. Under carbon-limited conditions, the yield of biomass from substrate was 0.76 g of biomass g of octanoate(-1) consumed, the yield of PHA was 0.085 g of PHA g of octanoate(-1) used, and 7.9 g of octanoate was consumed for each gram of NH(4)(+) supplied. The maintenance coefficient was 0.046 g of octanoate g of biomass(-1) h(-1). Replacement of sodium octanoate with octanoic acid appeared to result in transport-limited growth due to the water insolubility of the acid.